Nonstationary pearl pulsations as a signature of magnetospheric disturbances - F. Z. Feygin; F. Z. Feygin; F. Z. Feygin; N. G. Kleimenova; O. A. Pokhotelov; M. Parrot; K. Prikner; K. Mursula; J. Kangas; T. Pikkarainen (Annales Geophysicae, 2000)
We analyse long-lasting (several hours) Pc1 pearl pulsations with decreasing, increasing or constant central frequencies. We show that nonstationary pearl events (those with either decreasing or increasing central frequency) are observed simultaneously with increasing auroral magnetic activity at the nightside magnetosphere while the stationary events (constant central frequency) correspond to quiet magnetic conditions. Events with decreasing central frequency are observed mostly in the late morning and daytime whereas events with increasing central frequency appear either early in the morning or in the afternoon. We explain the diurnal distribution of the nonstationary pearl pulsations in terms of proton drifts depending on magnetic activity, and evaluate the magnetospheric electric field based on the variation of the central frequency of pearl pulsations. Key words: Magnetospheric physics (magnetospheric configuration and dynamics; plasma waves and instabilities)